Jimmi Iskandar SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA CV FARROS SABLON: Indonesia - Jimmiiskandar (Journal of Technology and Engineering, 2026)
This study aims to develop a Decision Support System to assist CV Farros Sablon in selecting the best employee. The selection of high-performing employees is essential for improving the company's productivity and the quality of its work outcomes. To enhance the decision-making process, this study employs the Analytical Hierarchy Process (AHP) method. The research stages include identifying employee selection criteria, constructing pairwise comparison matrices, ranking the criteria, and determining the best employee based on the results of AHP calculations. The data used in this study include employee attendance records, the number of printed products completed, the type of ink used, and the number of overtime hours worked by each employee. The results of this study are expected to provide objective and accurate recommendations to management in selecting outstanding employees. The implementation of this system is anticipated to improve operational efficiency, motivate employees to achieve higher levels of performance, and support the future growth and development of CV Farros Sablon.